Alleviation of Rock Bursts by Identifying Burst-Prone Mine Workings - S. Paul Singh (International Conference on Ground Control in Mining, 2008)
Rock burst is one of the most serious mining hazards, adversely affecting the safety, economy and productivity of mines. It is a sudden manifestation of the release of strain energy stored in the rock mass. At present, there is no universally accepted method for predicting the timing of the rock burst. However, if the seismically hazardous regions in mines can be identified before they are exposed to mining then precautionary measures can be planned before the work begins. A study was conducted in Sudbury Nickel Belt and an approach has been proposed to identify rock burst prone workings on the basis of (a) Rock properties and bursting indices (b) In-situ approaches (c) Geological features (d) Mining conditions (e) Observations during mining operations (f) Comparison and analogy with previous case histories of bursting. This approach will facilitate the judicious application of the burst control techniques to seismically hazardous areas.